2015
DOI: 10.1007/s12291-015-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

Status and Interrelationship of Zinc, Copper, Iron, Calcium and Selenium in Prostate Cancer

Abstract: Deficiency or excess of certain trace elements has been considered as risk factor for prostate cancer. This study was aimed to detect differential changes and mutual correlations of selected trace elements in prostate cancer tissue versus benign prostatic hyperplasia tissue. Zinc, copper, iron, calcium and selenium were analysed in histologically proven 15 prostate cancer tissues and 15 benign prostatic hyperplasia tissues using atomic absorption spectrophotometer. Unpaired two tailed t test/MannWhitney U test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…There is a scarcity of published data regarding the correlations of various bioelements in the serum of transplant recipients. In the study of Singh et al [26], Zn was found to have positive correlations with Se in prostate cancer [26], which corresponds with our results.…”
Section: Discussionsupporting
confidence: 92%
“…There is a scarcity of published data regarding the correlations of various bioelements in the serum of transplant recipients. In the study of Singh et al [26], Zn was found to have positive correlations with Se in prostate cancer [26], which corresponds with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies indicate that selenium deficiency may also play a significant role in the etiology of prostate cancer [37]. However, the function of selenium in the prostate has not as yet been specified.…”
Section: Discussionmentioning
confidence: 99%
“…The most common techniques used today for the quantification of Cu and Fe from biological samples in vitro and ex vivo include inductive coupling plasma mass spectrometry (ICP-MS) [209][210][211][212], atomic absorption spectrometry (AAS) [212,213], total reflection X-ray fluorescence (TXRF) [214,215], and colorimetric assays by UV-Vis measurements [216,217]. ICP-MS is a highly sensitive tool that allows the precise quantification of metal content down to sub parts per billion (ppb) levels using internal standards [218,219].…”
Section: Techniques To Quantify Cu and Fe Levelsmentioning
confidence: 99%